2014
DOI: 10.3928/01477447-20140626-52
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Using Titanium Elastic Nails for Open and Closed Pediatric Tibia Fractures

Abstract: The authors conducted a retrospective review at their level I trauma center to assess the outcomes of closed vs open pediatric tibial fractures treated with titanium elastic nails. The study group included 38 pediatric patients (median age, 12 years) treated with titanium elastic nails for tibial fractures during a 5-year period. Patient demographics, closed or open injury, Gustilo-Anderson type for open fractures, fracture location, skeletal maturity, time to union, hospital length of stay, number of procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 14 publications
(28 reference statements)
1
33
1
Order By: Relevance
“…Of the excluded full texts, the most common reason for exclusion was that open fractures could not be separated (10 studies) [19][20][21][22][23][24][25][26][27][28] followed by studies with too small population (7 studies). [29][30][31][32][33][34][35] In two studies, 36,37 distal tibia fractures were no distinguishable from diaphyseal fractures, and two studies 38,39 reported only the incidence of compartment syndrome. Three additional studies reporting only epidemiological data, 40 surgical technique, 41 and long-term outcomes, 42 respectively, were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Of the excluded full texts, the most common reason for exclusion was that open fractures could not be separated (10 studies) [19][20][21][22][23][24][25][26][27][28] followed by studies with too small population (7 studies). [29][30][31][32][33][34][35] In two studies, 36,37 distal tibia fractures were no distinguishable from diaphyseal fractures, and two studies 38,39 reported only the incidence of compartment syndrome. Three additional studies reporting only epidemiological data, 40 surgical technique, 41 and long-term outcomes, 42 respectively, were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical results are good; whichever treatment method is chosen but age is a consideration to define the best treatment 19, 20, 21, 22, 23, 24, 25. Closed reduction and plaster application is still the gold standard for tibial fractures in children.…”
Section: Discussionmentioning
confidence: 99%
“…Elastic stable intramedullary nailing is the gold standard for osteosynthesis of unstable diaphyseal fractures in children and adolescents 20, 27. In tibial fractures, indications for operative treatment are determined based on a variety of factors including fracture type, location, severity and patient age 22, 28. The encouraging results of elastic stable intramedullary nailing in femoral and forearm fractures led us to use this technique to treat tibial shaft fractures 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has advantages of not requiring pin site care, and both give access to the overlying leg tissue unless a cast is placed for rotational control or lack of cooperation. 19 Progressive weight bearing is allowed after 2–3 weeks with hip, knee, and ankle range of motion exercises from the outset. 16 17 Hardware is removed at 6–9 months, noting the temporary risk of refracture to warrant a delay in returning to full sporting activities.…”
Section: Treatmentmentioning
confidence: 99%